Ayaw kong maging querida - Garcia, Leonardo; Yabot, Rodolfo C.; Santos, Vilma; Vasquez, Romeo; Martin, Carmi (Ilang-Ilang Production, 2008)
A story about three people caught in a whirlwind romance bound in the norms of society class. will love conquer all or will wealth and power dictate their destinies?